Revision and phylogeny of Tarvaia Allgén, 1934 (Nematoda: Tarvaiidae) - Holovachov, O.; Fadeeva, N.; Tandingan De Ley, I.; Mundo-Ocampo, M.; Gingold, R.; De Ley, P. (Nematology, 2012)
Descriptions of eight new and three known species of Tarvaia are given. Tarvaia pacifica sp. n. has cephalic capsule reaching posterior part of short amphids, amphidial shield without ornamentation, straight vagina with pars refringens vaginae, slightly asymmetrical spicules, gubernaculum with two dorsal apophyses, precloacal ridge present; T. algicola sp. n. has cephalic capsule with unevenly thickened walls reaching posterior part of short amphids, amphidial shield without ornamentation, straight vagina, apophyses absent, precloacal ridge present; T. carolinensis sp. n. has cephalic capsule reaching posterior part of short amphids, amphidial shield with ornamentation, sigmoid vagina, gubernaculum with a dorsal apophysis; T. longispiculata sp. n. has elongated cephalic capsule reaching posterior part of elongate amphids, amphidial shield without ornamentation, sigmoid vagina, unusually long spicules, gubernaculum with dorsal apophysis, precloacal ridge present; T. inaequalis sp. n. has short cephalic capsule reaching anterior third of elongate amphids, amphidial shield with ornamentation, straight vagina, strongly anisometric spicules, gubernaculum with caudal apophysis, precloacal ridge present; T. sakhalinensis sp. n. has short cephalic capsule reaching middle of short amphids, amphidial shield with distinct pores, symmetrical spicules, apophyses absent; T. tchesunovi sp. n. has cephalic capsule with unevenly thickened walls reaching posterior part of short amphids, amphidial shield without ornamentation, symmetrical spicules, apophyses absent; and T. ricordensis sp. n. has cephalic capsule reaching posterior part of short amphids, amphidial shield without ornamentation, straight vagina, symmetrical spicules, gubernaculum with dorsal apophyses. Updated descriptions of T. donsi, T. cladara and T. gerlachi are provided. Phylogenetic analysis based on 18S rDNA suggests a close relationship between Tarvaia and Desmoscolecida.